(3GdYSLO GdeSHhc hGdLhgQ GdeMchc aj WHbGJ GdNdaGA hGdedhcs - (3ESeGYjd Hf GdYHGS Hf Ydj , GdQShdj , GdCTQa,J (B803 (3g` s
(3ChdgG (B:s
(3ebOeI GdcJGH ai PcQ QShd Gddg Udi Gddg Ydjg hSde ajgG KeGfjI YTQ aUdkG GdaUd GdChd ai PcQ fSH QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3ef GdaUd GdQGHY hGdYTQjf ai PcQ NdGaI GdeSJcai bhdg (B: (3aOHQ Ydjg MJi bHV Ydjg hGSJaJi GdabgGA aCaJhG HEHGMI Oeg hai gPg GdSfI ONd Sja GdOhdI MdH eZGdHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B275s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B148 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs